Proposing Structured Input Activities for Communicative Grammar Teaching - Sulistyani Sulistyani; Khoiriyah Khoiriyah (Universitas PGRI Madiun, 2016)
Current views of language teaching suggest that grammar is included in communicative activities. The reason is that discrete grammar teaching fails to produce fluent speakers while pure communicative classroom fails to produce accurate speakers. This article aims to share a way of teaching grammar in meaning-focused instruction namely structured input activities consisting of referential activities and affective activities. The activities not only affect learners’ input processing strategies but also affect their underlying system in such a way to be able to incorporate the target forms in their output. Besides containing input that facilitates form meaning connections they also force learners to focus on the target structure and to process it for meaning. This practice is expected to provide EFL teachers with useful practical insight to enhance their teaching practices.